THE TOURISM SYSTEM – MAIN DIRECTIONS IN EVALUATING ITS OPERATION - MIHAI IELENICZ; SMARANDA SIMONI (Revue Roumaine de Géographie)
Tourism represents a complex system,with dynamic, geographic, temporaland unitary structure and functionality. It has various components ofdifferent influences according to the human interest determined by the social, economic, scientific and political conditions of the moment. Tourism implies special investigation and valuation on the crossing point of representatives from different fields of activities and diverse levels of the system hierarchically arranged.Tourism activities also imply quantitative and qualitative evaluations for the use of authorities, tourism operators, communities and tourists (influencing their decision-making process). Minute investigations, quantification and selection of tourism patrimony elements are essential in its valuation programs and regional socio-economic development programs. The paper deals with these considerations, providing a synthesis in tables and figures to analyse tourism activity.